Thirty-year retrospective on language, gender and sexuality research. (13th July 2021) - Hall, Kira; Borba, Rodrigo; Hiramoto, Mie
Abstract : This thirty-year retrospective on language, gender and sexuality research, launched in anticipation of the thirtieth anniversary of the 1992 Berkeley Women and Language Conference, showcases essays by luminaries who presented papers at the conference as well as allied scholars who have taken the field in new directions. Revitalising a tradition set out by the First Berkeley Women and Language Conference in 1985, the four biennial Berkeley conferences held in the 1990s led to the establishment of the International Gender and Language Association and subsequently of the journal Gender and Language, contributing to the field's institutionalisation and its current pan-global character. Retrospective essays addressing the themes of Politics, Practice, Intersectionality and Place will be published across four issues of the journal in 2021. In this second issue on the theme of practice, Deborah Tannen, Penelope Eckert, Marjorie Harness Goodwin, and Elinor Ochs and Tamar Kremer-Sadlik show how the field's attention to the micro-details of situated, highly contextualised interaction offers a privileged vantage point for seeing how gender, power and other dimensions of social life emerge as mundane daily actions unfold. Shigeko Okamoto and Marcyliena H. Morgan review how research on the language practices of Japanese and African American women have been formative to the field while also describing the critical necessity of more attention to these areas moving forward. The theme series also pays tribute to significant scholars present at the 1992 Berkeley conference who are no longer with us; in this issue, Heidi E. Hamilton pays homage to the groundbreaking work of Deborah Schiffrin.